Study on the Antimicrobial Properties of Surface-Modified Dental Implants - Jeeth Rai; Anju N Kilari; Himanshi Sachdev; Waseem A. Quazi; Bharani K. Bhattu; Naina Pattnaik; Miral Mehta; Laxmikant Late (Journal of Pharmacy and Bioallied Sciences)
Background: Dental implants have revolutionized restorative dentistry, but peri-implantitis caused by bacterial colonization remains a significant challenge. Surface modification of implants has emerged as a promising strategy to enhance their antimicrobial properties, ensuring better long-term outcomes. This study evaluates the antimicrobial efficacy of surface-modified dental implants against common oral pathogens. Materials and Methods: Thirty dental implants were divided into three groups: Group A (unmodified titanium implants), Group B (titanium implants coated with silver nanoparticles), and Group C (titanium implants coated with zinc oxide nanoparticles). The antimicrobial activity of each group was assessed using an agar diffusion test against Streptococcus mutans and Porphyromonas gingivalis. Colony-forming units (CFUs) were counted after 48 hours of incubation. Statistical analysis was performed using ANOVA to compare the antimicrobial efficacy between groups, with a significance level set at P < 0.05. Results: Group A showed minimal antimicrobial activity, with mean inhibition zones of 1.5 ± 0.3 mm for S. mutans and 1.2 ± 0.4 mm for P. gingivalis. Group B exhibited significantly higher antimicrobial activity, with mean inhibition zones of 10.5 ± 0.8 mm for S. mutans and 9.3 ± 0.7 mm for P. gingivalis (P < 0.05). Group C demonstrated moderate activity, with inhibition zones of 6.8 ± 0.5 mm for S. mutans and 5.9 ± 0.6 mm for P. gingivalis. The reduction in CFUs followed a similar trend, with Group B showing the highest reduction. Conclusion: Surface-modified dental implants, particularly those coated with silver nanoparticles, exhibit enhanced antimicrobial properties compared to unmodified implants. This suggests that incorporating antimicrobial coatings can be a viable strategy to reduce peri-implantitis and improve implant success rates. Further in vivo studies are recommended to validate these findings.